2005
DOI: 10.1136/jnnp.2004.056606
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variability in familial prion diseases due to the D178N mutation

Abstract: patients with familial prion diseases due to the D178N mutation were referred to the regional epidemiological registry for spongiform encephalopathies in the Basque Country in Spain, a small community of some 2 100 000 inhabitants. Methods: Ten further patients belonging to the same pedigrees were retrospectively ascertained through neurological or neuropathological records. In four of the patients, the diagnosis was confirmed by analysing DNA obtained from paraffin blocks. In this article, we report on the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
3
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 17 publications
5
85
3
4
Order By: Relevance
“…2,4 An influence of the M129V genotype on disease duration was seen in our FFI patients, a finding that corresponds to the longer survival associated with the MV genotype compared with the MM genotype in sCJD. 15 Whereas Montagna and colleagues 6 reported similar data, Harder and coauthors 3,16 did not ob- serve any significant association between disease duration and genotype at codon 129.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…2,4 An influence of the M129V genotype on disease duration was seen in our FFI patients, a finding that corresponds to the longer survival associated with the MV genotype compared with the MM genotype in sCJD. 15 Whereas Montagna and colleagues 6 reported similar data, Harder and coauthors 3,16 did not ob- serve any significant association between disease duration and genotype at codon 129.…”
Section: Discussionmentioning
confidence: 86%
“…The diagnostic importance of polysomnography in FFI noted in our study has been emphasized by other authors. 2,6,12,14 [ 18 F]FDG-PET studies were reported to support FFI diagnosis. 9 Selective thalamic changes were seen on PET in only two of our patients, whereas widespread cortical hypometabolism without clear preference for a particular cortical region was found in five patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The D178N mutation can trigger different clinico‐pathological syndromes, either thalamic‐dominant FFI or CJD, depending on a methionine‐valine polymorphism at PRNP codon‐129 8, 9, 10. FFI syndrome is almost exclusively associated with methionine in the mutated allele (D178N‐129M),9 but not all the carriers of the D178N‐129M mutation develop an FFI phenotype 11, 12. Additionally, methionine/valine polymorphism in the normal allele appears relevant for disease progression and severity, with FFI D178N‐129 M/M patients presenting with a more rapid decline compared to D178N‐129 M/V cases 9.…”
Section: Introductionmentioning
confidence: 99%